Benchmarking methodology in a transport sector - Išoraite, Margarita (Transport, 2004)
The article analyses the following issues: 1) Definitions of benchmarking. Benchmarking as a management tool that has long been succefully used both in the private and public sectors to improve the efficiency and effectiveness of products and processes; 2) Benefits of transport benchmarking. Benchmarking can help transport enterprise to: locate its strengths, pinpoint weaknesses, measure its performance against its competitors, discover what it is possible to achieve; 3) Different types of benchmarking. Different types of benchmarking processes can be distinguished into performance benchmarking, process benchmarking, strategic benchmarking, competitor benchmarking, functional benchmarking, generic benchmarking; 4) Transport benchmarking methodology. The basic transport benchmarking principles – planning, analysis, integration, action and recycle are equally valid for transport policy benchmarking; 5) Key performance indicators in a transport sector.First Published Online: 27 Oct 2010